Аналіз безпеки ЦП на основі геш функції Keccak - Івашов, В. А. (ХНУРЕ, 2024)
An analysis of the security of digital signatures using the Keccak hash function was carried out in order to determine their resistance to modern cryptanalytic attacks and justify their suitability for protecting digital information. Analysis of the security of a digital signature includes an assessment of the resistance of such a signature to various attacks, including cryptanalysis, collisions, and other types of attacks on the hashing algorithm and the signature scheme itself.
Keywords: геш функція Keccak; Keccak hash function